Factors influencing the utilisation of antenatal care services in the Manhyia sub-metro, Kumasi - Yegbe, Afia Seiwaa (2016)
A thesis submitted to the Department of Health Policy, Management and Economics College of Health Science, School of Public Health, in partial fulfillment of the requirements for the degree of Master of Public Health in Health Services Planning and Management,